Cultivating Critical Thinking as Habitus through Student Research Programs in Madrasah Education - Cahyani, Syifa Amalia Geanti; Fajar, Fajar (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
The research aims to analyze how research-based pedagogy functions as an arena in which critical thinking is cultivated, embodied, and sustained as a patterned way of thinking, acting, and positioning oneself intellectually. Using a qualitative approach, data were generated through prolonged observation, in-depth interviews with teachers, research mentors, and student participants, and document analysis. The analytical process followed an interactive model of data condensation, display, and iterative interpretation to illuminate the mechanisms through which critical thinking dispositions are socially produced and reinforced. The findings indicate that student research programs operate not merely as extracurricular enrichment but as continuous pedagogical practices that institutionalize inquiry, dialogic reflection, collaborative problematization, and public argumentation. Through repeated engagement in identifying problems, constructing evidence-based arguments, negotiating meaning, and presenting findings, students internalize critical inquiry as a normative and embodied orientation. Supporting structures such as sustained mentoring and an academically competitive climate strengthen this habituation process, while temporal and environmental constraints may disrupt its continuity. This study contributes by advancing an understanding of critical thinking as a socially cultivated habitus rather than a momentary cognitive outcome, thereby offering a conceptual framework for reimagining research-based pedagogy in madrasah education and beyond.